Movement Disorders in Brazil: the seminal contributions of Luiz Augusto Franco de Andrade and Egberto Reis Barbosa - Teive, Hélio Afonso Ghizoni; Ferraz, Henrique Ballalai; Limongi, João Carlos Papaterra; Franklin, Gustavo Leite; Cardoso, Francisco Eduardo Costa (Arquivos de Neuro-Psiquiatria, 2021)
The major advances in the area of movement disorders in Brazil in recent years were driven by the work of Luiz Augusto Franco de Andrade and Egberto Reis Barbosa. This historical review describes the contributions made by these researchers, physicians, and educators to the development of this field in Brazil.
Keywords: History of Medicine; Neurology; Movement Disorders; Basal Ganglia Diseases